2021
DOI: 10.1038/s41598-021-03623-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of reverse transcription-loop-mediated isothermal amplification for rapid detection of SARS-CoV-2

Abstract: The main strategy for response and control of COVID-19 demands the use of rapid, accurate diagnostic tests aimed at the first point of health care. During the emergency, an increase in asymptomatic and symptomatic cases results in a great demand for molecular tests, which is promoting the development and application of rapid diagnostic technologies. In this study, we describe the development and evaluation of RT-LAMP to detect SARS-CoV-2 based on three genes (ORF1ab, M and N genes) in monoplex and triplex form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
4
1
Order By: Relevance
“…In contrast, the previously established TiPV qPCR assay showed a detection limit at 2.56 × 10 1 copies/μL (Yamkasem et al, 2022), while the TiPV LAMP in this study showed the detection limit at 5.25 × 10 3 copies/ μL. Other LAMP assays have revealed detection limits between 10 and 100 copies for the detection of viruses (Baek et al, 2020;Lu et al, 2020;Park et al, 2020;Quino et al, 2021). Although LAMP assays are reliable and sensitive in detecting TiPV-infected fish, the qPCR assay had 100-times higher sensitivity than the LAMP assay.…”
Section: Sensitivity Of the Tipv Lamp Assaycontrasting
confidence: 97%
“…In contrast, the previously established TiPV qPCR assay showed a detection limit at 2.56 × 10 1 copies/μL (Yamkasem et al, 2022), while the TiPV LAMP in this study showed the detection limit at 5.25 × 10 3 copies/ μL. Other LAMP assays have revealed detection limits between 10 and 100 copies for the detection of viruses (Baek et al, 2020;Lu et al, 2020;Park et al, 2020;Quino et al, 2021). Although LAMP assays are reliable and sensitive in detecting TiPV-infected fish, the qPCR assay had 100-times higher sensitivity than the LAMP assay.…”
Section: Sensitivity Of the Tipv Lamp Assaycontrasting
confidence: 97%
“…While the study presented here is limited to synthetic RNA control templates, the choice of optimal primer set and the sensitivity benefit of primer set combination is a fundamental starting point for any diagnostic assay. The benefit of combining RT-LAMP primer sets for increased sensitivity as we described in [10] has since been demonstrated with extracted RNA and directly from clinical samples [21][22][23][24] and thus we believe the analysis of many additional potential primer sets described here is of benefit to additional assay development. SARS-CoV-2 unfortunately remains a significant public health concern with continuing needs for diagnostic and surveillance testing, increasingly in field, point-of-care, and even home settings removed for traditional clinical laboratory infrastructure where RT-LAMP is particularly valuable.…”
Section: Plos Onementioning
confidence: 86%
“…In contrast, real-time fluorometric detection offers greater sensitivity, efficiency, precision, and the possibility of quantifying viral loads [ 18 , 19 ]. Several studies have reported RT-LAMP assays for the detection of SARS-CoV-2 [ 20 25 ]. However, most of these use commercial reaction mixtures and enzymes subjected to availability that can limit diagnostic tests during the pandemic [ 26 ].…”
Section: Introductionmentioning
confidence: 99%